The combination treatment of RC48 and STAT3 inhibitor acts as a promising therapeutic strategy for basal bladder cancer - Li, Jingxian; Shan, Kun; Huang, Wei; Su, Qiang; Qi, Yuanjiong; Zhang, Zhihong; Zhu, Jianqiang; Du, E. (Frontiers in Immunology, 2025)
As an antibody-drug conjugate (ADC), disitamab vedotin (RC48) is a promising treatment targeting ERBB2 for locally advanced and metastatic bladder cancer (BLCA). However, the subtype heterogeneity of muscle-invasive bladder cancer (MIBC) often leads to different therapeutic outcomes. In our study, we aim to explore sensitivity differences and mechanisms of different molecular subtypes of MIBC to RC48 treatment and develop a strategy for combination therapy against cancer. Using large-scale mRNA expression profile datasets, Western blotting, and immunohistochemistry, we first found that ERBB2 is upregulated in the luminal type but downregulated in basal bladder cancer. In addition, luminal cells showed higher sensitivity to RC48 than basal cells. Basal cells with ERBB2 overexpression demonstrated increased sensitivity to RC48 in vitro and in vivo, indicating that ERBB2 expression mediates RC48’s therapeutic efficacy against cancer. In basal or RC48-exposed luminal cells, the JAK/STAT3 pathway was highly enriched, suggesting that downregulation or pharmacological inhibition of ERBB2 leads to compensatory activation of this pathway. Silencing STAT3 increased the inhibitory efficacy of RC48. In addition, artesunate (ART, a STAT3 inhibitor) showed a synergistic effect with RC48 against basal bladder cancer both in vitro and in vivo. In summary, these findings provide a theoretical foundation for subsequent clinical trials combining RC48 and ART in MIBC based on molecular subtypes.